2014
DOI: 10.1039/c4ra09582k
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of process parameters and various modes of application of TiO2 nanoparticles in heterogeneous photocatalysis of pharmaceutical wastes – a short review

Abstract: In recent years, the occurrence of persistent organic compounds in industrial as well as municipal effluents is becoming a serious threat to the environment. The detrimental effects can be minimized with the help of photocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 88 publications
1
34
0
1
Order By: Relevance
“…Several immobilization techniques are adopted to reuse and recycle the nano particles, among them immobilization of nano particle on the membrane surface has become promising technique (Sarkar et al, 2014b). Earlier studies have shown that membrane can be used for immobilization of foreign material to incorporate catalytic property on the membrane surface (Ho and Zydney, 2000;Nunes et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Several immobilization techniques are adopted to reuse and recycle the nano particles, among them immobilization of nano particle on the membrane surface has become promising technique (Sarkar et al, 2014b). Earlier studies have shown that membrane can be used for immobilization of foreign material to incorporate catalytic property on the membrane surface (Ho and Zydney, 2000;Nunes et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In past decades, titanium dioxide (TiO 2 )-based heterogeneous photocatalysis has been used for the efficient degradation of organic compounds, dyes, pesticides and pharmaceuticals [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Advanced Oxidation Processes (AOPs) based on generation of strongly reactive hydroxyl radicals ( * OH) have received a large interest for the removal of pharmaceuticals from waste water [8][9][10]. Among the AOPs, heterogeneous photocatalysis is considered as a promising process for pharmaceuticals active ingredients treatment operating under ambient temperature and pressure [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%